A BPW-Hungária Kft. logisztikai tevékenysége - Szakács Georgina (2015)
Logistics plays a fundamental role in the life of firms in the 21th century. The company's successful operation, it is important to monitor the internal and external surroundings, the changes and improvements to be open, the problems that may occur as the legoptimáli-sabban and quickly solves. A mature logistic system that is well-structured and organised ensures the firm’s long-term competiteve subsistence, its succes int he enterprise competition sphere, so I decided to become absorbed in this topic. In my thesis work I would like to represent the logistic activity of BPW-Hungary Ltd. BPW-Hungária Ltd., the subsidiary of the German company, BPW-Bergische Achsen KG in Szombathely is an important player in the field of automotive industry in West Transdanubian Region. Headquarters of parent company is located in Wiehl in Germany. This company manufactures high-quality running gears and suspencion systems for towed vehicles that are well-known all over the world, as well as products of agricultural and engineering industry, furthermore it is concerned with the deisgn and development of agriculural products. One of its outstanding significance for the disc brakes, drum brakes and steering axle and the rigid and steering axles. My professional practice by the company explains why I chose this topic for my thesis work. I had the opportunity to insight into many aspects of the company, as well as to gain extensive knowledge concerning the sphere of procurement, stockpiling and storage. These three aspects of logistics are of decisive importance because all of these can have a great effect on the optimal operation of the company. The aim of my thesis is to represent the operation of the company’s procurement, stockpiling and storage and I would like to make a proposal how to reconcile certain waves concerning stock application in order to achieve a steady and balanced operation. While writing my dissertation I tried to use my personal experiences as well as professional practice and knowledge in the highest degree. The essay writing in-depth interviews, literature, journals and internet resources were used. The bright interviews, literature, Internet resources, and journals I applied it.